It’s fucking 80 years after Duchamp - Øster Larsen, Lene (Peripeti, 2024)
Through an analysis of Danish artist Jakob Boeskovs work »My Doomsday Weapon«, Lene Øster Larsen explores the implications and possibilities of political and interventionist artistic tactics.